PSYCHOLOGICAL AND EDUCATIONAL SUPPORT PROJECT ACTIVITIES OF STUDENTS IN THE INNOVATION AREA - L. V. Liaminа (Вестник Мининского университета, 2017)
The article discusses the features of the creation of innovative platforms - student business incubator as a form of design activity of students and the organization of their psycho-pedagogical support. The innovative platform - a form of a special organization of innovative activity, promoting the development of skills in terms of design, including elements of the strategy development, consulting, expertise. The experience of the creation in 2011 at the Bashkir State Pedagogical University. M. Akmulla innovation platform - a student business incubator, whose main purpose is to support innovative projects of students, including two strategic areas: education and investment. Analyzes the positive experience of the formation of creative thinking of students in the area of innovation activities, because in it there is the possibility of creating resources for the enrichment of the subjective experience of the student. Outlined the conditions for the development of creative activity of students.